Professional Development in ICT: Analysis of Training and Usefulness for Guidance Counselors in Public Schools in Costa Rica - Daniela Morera-Ulate; Dana Angélica Navarro-Bonilla; José Antonio García-Martínez (Revista Costarricense de Orientación, 2025)
Objective: This article analyzes the professional development in Information and Communication Technologies (ICT) and the institutional support for guidance counselors in public schools in Costa Rica.